2022
DOI: 10.1177/17455057221103098
|View full text |Cite
|
Sign up to set email alerts
|

US Black cisgender women and pre-exposure prophylaxis for human immunodeficiency virus prevention: A scoping review

Abstract: Background: Black cisgender women in the United States experience a disproportionate burden of human immunodeficiency virus acquisition. Pre-exposure prophylaxis is an effective oral daily medication that reduces the risk of human immunodeficiency virus through sex by 99% when taken as prescribed. However, less than 2% of eligible Black cisgender women take pre-exposure prophylaxis. The purpose of this scoping review was to describe the types of research studies done in this area, gaps in knowledge, and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Upon full completion of training, stylists received a certificate of completion and "Ask Me about PrEP" signage for their beauty salons to facilitate conversations with women. Second, together with the community, an edutainment series (The Wright Place) was co-developed with Black women and an established community advisory council (Randolph et al, 2022). The series uses culturally and socially relevant stories to highlight key messages about (a) HIV, (b) PrEP, and (c) Black women's social contributors to health.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon full completion of training, stylists received a certificate of completion and "Ask Me about PrEP" signage for their beauty salons to facilitate conversations with women. Second, together with the community, an edutainment series (The Wright Place) was co-developed with Black women and an established community advisory council (Randolph et al, 2022). The series uses culturally and socially relevant stories to highlight key messages about (a) HIV, (b) PrEP, and (c) Black women's social contributors to health.…”
Section: Methodsmentioning
confidence: 99%
“…This multicomponent, mixedmethods study used a community-engagement approach to develop and pilot test a salon-based intervention, UPDOs. Study procedures were previously reported (Randolph et al, 2022). Eligibility criteria included (a) age 18 years or older, (b) frequency of visiting the salon at least every 2 weeks, (c) self-identification as Black or African American, (d) self-identification as a woman, and (e) ability to speak and read English.…”
Section: Sample and Settingmentioning
confidence: 99%
See 1 more Smart Citation